Survey of Leftover Drugs among Patients with Chronic Diseases at Bangsaphan Hospital, Prachuap Kirikhan. - ฉันทภัทรางกูร พุทธชาติ; ทองโปร่ง ศิระพร; ทองมี มนูญ (Hua Hin Medical Journal, 2019)
This survey research aimed to study the items, quantity and the cause of the Leftover drugs in 500 chronic disease patients at chronic disease clinic, OPD department, Bangsaphan Hospital between January – July 2018. Use descriptive statistic to analyse and report the data, the study were the most of patients were female 65.6% male 34.4% age 60-69 years 50.0% the average age was 65+0.24 years. The diabetes mellitus and hypertension 50.0%, graduated primary school 70.0% and used gold patent 70.0%. The most of leftover drugs were metformin 500 mg amlodipine 10 mg and enalapril 5 mg 10.00% 9.33% and 8.67% respectively. The main cause of leftover drugs, were the doctor prescribe over drugs, non compliance patients, the doctor prescribe off the drugs 59% 21% and 10% respectively. From this study, the pharmacist could know the items and the causes of leftover drugs due to find the optimum quantity drugs for prescribing. The value of good drugs could reduce the drugs budget and due to monitor the patients for worth and safety.